2022
DOI: 10.21203/rs.3.rs-2107395/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resurgence of Omicron BA.2 in SARS-CoV-2 infection-naive Hong Kong

Abstract: After keeping infections at bay for two years, Hong Kong experienced a surge of Omicron BA.2 infections in early 2022 that overwhelmed the health care system, isolation facilities, and contact tracing capacity, leading to one of the highest per-capita death rates of COVID-19 in early 2022. The outbreak occurred against a backdrop of a dense population with low immunity towards natural SARS-CoV-2 infection, high vaccine hesitancy in vulnerable populations, comprehensive disease surveillance and the capacity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…The prevalence of long COVID in this study was similar to a systematic review (45%) that included over 0.7 million patients from different countries and infected by different variants of concern (wild‐type, Alpha, and Beta), 3 but lower than a study from China, where the prevalence of long COVID infected by various variants (wild‐type, Alpha, Beta, Delta, and Omicron) among mostly hospitalized patients was 90.4% 26 . The SARS‐CoV‐2 subvariants were not detected for patients in our study, the majority of COVID‐19 cases in the fifth wave of the Hong Kong outbreak were caused by Omicron BA.2 and related sublineages, the largest monophyletic lineage was BA.2.2, and only with limited detection of Omicron BA.1 and related sublineages and Delta AY.127 12 . A systematic review indicated that the prevalence of Omicron‐induced long COVID in 3 months (28.4%) was lower than other strains (wild‐type: 52.1%, Alpha: 65.8%, Delta: 34.6%) 27 .…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The prevalence of long COVID in this study was similar to a systematic review (45%) that included over 0.7 million patients from different countries and infected by different variants of concern (wild‐type, Alpha, and Beta), 3 but lower than a study from China, where the prevalence of long COVID infected by various variants (wild‐type, Alpha, Beta, Delta, and Omicron) among mostly hospitalized patients was 90.4% 26 . The SARS‐CoV‐2 subvariants were not detected for patients in our study, the majority of COVID‐19 cases in the fifth wave of the Hong Kong outbreak were caused by Omicron BA.2 and related sublineages, the largest monophyletic lineage was BA.2.2, and only with limited detection of Omicron BA.1 and related sublineages and Delta AY.127 12 . A systematic review indicated that the prevalence of Omicron‐induced long COVID in 3 months (28.4%) was lower than other strains (wild‐type: 52.1%, Alpha: 65.8%, Delta: 34.6%) 27 .…”
Section: Discussioncontrasting
confidence: 50%
“…26 The SARS-CoV-2 subvariants were not detected for patients in our study, the majority of COVID-19 cases in the fifth wave of the Hong Kong outbreak were caused by Omicron BA.2 and related sublineages, the largest monophyletic lineage was BA.2.2, and only with limited detection of Omicron BA.1 and related sublineages and Delta AY.127. 12 A systematic review indicated that the prevalence of Omicron-induced long COVID in 3 months (28.4%) was lower than other strains (wild-type: 52.1%, Alpha: 65.8%, Delta:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Hong Kong's fifth and largest COVID-19 wave was triggered by separate HQ transmissions of BA.2 outside the study period. 33 This wave comprised more than 1.1 million cases and over 9000 deaths, 34 demonstrating the potentially severe consequences of low-frequency HQ transmission events. Additionally, there have been other introductions of novel lineages in Hong Kong where the source could not be identified despite strict quarantine measures, including the unidentified introduction(s) which resulted in the third epidemic wave in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%